Malaysian's acceptance towards the multipurpose smart national identity card and driving license - Yeow, , Paul H. P; Loo, , W. H.; Chong, , S. C. (2006)
This paper investigates the users' acceptance towards two applications of Malaysian government's multipurpose smartcard (MyKad) i.e. national identity card (NIC) and driving license (DL). Seventy samples were collected through a questionnaire survey and analyzed using descriptive statistics. Results show no strong evidence that Malaysians accept the applications. The factors influencing the acceptance of MyKad NIC are security, privacy, convenience, monetary concerns, and durability. The factors influencing the acceptance of MyKad DL are the inconvenience of using card reader and renewing at limited places, the non-recognition by enforcement officers, and the lack of understanding in the benefits of the card. Recommendations to increase the acceptance of MyKad include clarifying the misconception that MyKad invades privacy, ensuring that enforcement officers carry a card reader during operation, and having promotion campaigns advocating the benefits of MyKad. The study is useful for other countries to increase the acceptability of their government's multipurpose smartcard applications.